K-Wiring Versus Plating: A Comparative Study on the Outcomes in Distal Radius Fractures - Mohammed Akhtar Khan, Basharat Ali, Mohammad Yusuf, Bilal Khursheed, Mohammad Omar Farooq, Niaz Muhammad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Distal radius fractures are among the most common orthopedic injuries, yet the optimal surgical management remains a topic of debate. This study compares the functional outcomes of two prevalent techniques: K-wire fixation and volar locking plate. Methods: A prospective randomized controlled trial was conducted from January to December 2022. Sixty eligible patients with closed AO type A or B DRFs were randomly allocated to either K-wire fixation (Group A, n=30) or volar plating (Group B, n=30). The primary outcome was the QuickDASH score at six months. Secondary outcomes included radiological parameters and complication rates (infection, malunion, hardware irritation, reoperation). Data were analyzed using SPSS version 25 independent t-tests and chi-square tests. P-value <0.05 considered significant. Results: The mean age of participants was 37.92 ± 10.07 years, with a male predominance (76.7%). The volar plating group demonstrated a statistically significant superior functional outcome, with a mean QuickDASH score of 13.01 ± 4.60 compared to 20.66 ± 4.96 in the K-wire group (p < .001). This functional advantage was consistent across most subgroups, particularly in younger and male patients. While overall complication rates were not significantly different, distinct trends were observed: the K-wire group had higher incidences of malunion (23.3% vs. 10.0%) and hardware irritation (40.0% vs. 26.7%), whereas the volar plating group had a higher reoperation rate (23.3% vs. 13.3%). Conclusion: Volar locking plate fixation for distal radius fractures results in significantly better functional outcomes at six months compared to K-wire fixation. However, there was no significant difference in the complications of both techniques. Keywords: Distal Radius Fracture, K-wire, Volar Locking Plate, Functional Outcome, Randomized Controlled Trial.